Consumer Perceptions of Sustainable Brand Positioning in Online Fast Fashion Retailers - Ibrar (My University, 2026)
The study examines the aspect of consumer trust and purchase intention about sustain-able brand positioning in the online fast-fashion sector. Quantitative research design was used, and data were collected with regard to 100 respondents using an online structured questionnaire. To evaluate the relationship between the constructs, statistical tests employing a descriptive analysis, reliability encompassing tests, factor analysis, multiple regression, and moderation modelling were utilised. The results show that consumer trust is most strongly dependent on the perceived authenticity, which means that clear and verifiable sustainability assertions have a strong impact on increasing credibility. Trust, in its turn, has a positive im-pact on purchase intention, but social media influence is even more active, which implies the significance of external digital clues in online buying scenarios. Moderation tests explain that the effect of trust on purchase intent is reinforced by greenwashing awareness, such that knowledge is rewarded by always choosing the brand that seems to be dedicated to sustain-ability sincerely. On the other hand, subjective norms and perceived authenticity have no moderating effects on the trust-intention relationship but have a significant direct impact on the purchase intention. The research has theoretical implications in that the author has combined attributional, signalling, and behavioural perspectives to elucidate sustainability decision-making and provided actionable information to brands, policymakers and regulators, who seek to establish credibility and create sustainable consumption. Limitations are being recognised, and future research suggestions are to be longitudinal, cross-cultural comparison, and a broader moderation model. Altogether, the paper highlights the pivotal role of authenticity and trust as the key messages in sustainability communication and indicates the changing complexity of consumers to judge environmental discourse.
Keywords: fast fashion; social media influencers; attribution theory; consumer behaviour; fi=Taloustiede|en=Economics|; Master’s Programme in Strategic Business Development